Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.